Variable primary coordination environments of Cd(ii) binding to three helix bundles provide a pathway for rapid metal exchange. Issue 12 (27th October 2015) - Tebo, Alison G.; Hemmingsen, Lars; Pecoraro, Vincent L.
Abstract : Members of the ArsR/SmtB family of transcriptional repressors, such as CadC, regulate the intracellular levels of heavy metals like Cd(ii ), Hg(ii ), and Pb(ii ). Abstract : Members of the ArsR/SmtB family of transcriptional repressors, such as CadC, regulate the intracellular levels of heavy metals like Cd(ii ), Hg(ii ), and Pb(ii ). These metal sensing proteins bind their target metals with high specificity and affinity, however, a lack of structural information about these proteins makes defining the coordination sphere of the target metal difficult. Lingering questions as to the identity of Cd(ii ) coordination in CadC are addressed via protein design techniques. Two designed peptides with tetrathiolate metal binding sites were prepared and characterized, revealing fast exchange between CdS3 O and CdS4 coordination spheres. Correlation of 111m Cd PAC spectroscopy and 113 Cd NMR spectroscopy suggests that Cd(ii ) coordinated to CadC is in fast exchange between CdS3 O and CdS4 forms, which may provide a mechanism for rapid sensing of heavy metal contaminants by this regulatory protein.